Preconception-related needs of reproductive-aged women. (February 2016) - Goossens, Joline; Delbaere, Ilse; Dhaenens, Celine; Willems, Lies; Van Hecke, Ann; Verhaeghe, Sofie; Beeckman, Dimitri
Abstract: Objective: to assess women׳s interest in preconception care, their organisational preferences, and their preconception-related information and support needs. Design: cross-sectional study design. Setting: participants were recruited online through social media and discussion forums for issues relating to (in)fertility, pregnancy and parenting, and at the Women׳s Clinic of Ghent University Hospital. Participants: 242 reproductive-aged women with a desire to have (more) children. Findings: the majority of women (75%) wanted to receive preconception care in the future. Gynaecologists (93%) were the preferred source of preconception care, followed by midwives (73%) and general practitioners (63%). Most women wanted information about lifestyle, environmental exposures, working conditions and medical issues. Information needs were higher among women with (history of) mental illness [odds ratio (OR) 3.50, 95% confidence interval (CI) 1.08–11.36], (history of) eye and otolaryngological problems (OR 2.22, 95% CI 0.95–5.21) and overweight (OR 2.22, 95% CI 1.01–4.93). A few women indicated that they needed preconception-related support. Overweight women reported greater need for lifestyle-related support compared with women of healthy weight ( p =0.001). Key conclusions: reproductive-aged women are interested in preconception care, and would prefer to receive this care directly from a professional caregiver. Most women had high preconception-related information needs and lower support needs. Implications for practice: although women reported that they would prefer to receive preconception care from gynaecologists, the results indicate that midwives can also play an important role in the provision of preconception care. They would need further training to improve their knowledge, skills and awareness regarding preconception care. Highlights: Most women were interested in receiving preconception care in the future. The gynecologist was the most preferred source for preconception care. The preconception-related information need was high, and the support need low. Women with medical conditions had higher information and support needs.